1999
DOI: 10.1007/s004649901043
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of immunologic and physiologic effects of CO2 pneumoperitoneum at room and body temperatures

Abstract: The authors conclude that intraoperative cooling can be prevented by warming the insufflation gas, even in short laparoscopic procedures. In addition, warming the insufflation gas leads to a reduced postoperative intraperitoneal cytokine response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 14 publications
0
43
0
3
Order By: Relevance
“…However, the decrease in temperature was not statistically significant. Other investigators have found that the use of unheated CO 2 for peritoneal insufflation can be associated with a decrease in body temperature and that the use of warm CO 2 prevented hypothermia and blunted the cytokine response [18]. Another study in adults showed that nasopharyngeal temperature increased after 1 h of pneumoperitoneum with heated CO 2 [20].…”
Section: Discussionmentioning
confidence: 92%
“…However, the decrease in temperature was not statistically significant. Other investigators have found that the use of unheated CO 2 for peritoneal insufflation can be associated with a decrease in body temperature and that the use of warm CO 2 prevented hypothermia and blunted the cytokine response [18]. Another study in adults showed that nasopharyngeal temperature increased after 1 h of pneumoperitoneum with heated CO 2 [20].…”
Section: Discussionmentioning
confidence: 92%
“…[25] The passage of CO2 through the insufflator and tubing apparatus raises this temperature to approximately room temperature (19°C-21°C) at the point of delivery to the peritoneal cavity with a relative humidity approaching 0% at the point of entry into the peritoneal cavity. [34][35][36] However, this still is significantly lower than the normal intraperitoneal or core temperature. Large volumes of gas may be required for a single patient (up to 500 litres), owing to the imperfect seal of the laparoscopic ports and peritoneal CO2 absorption.…”
Section: Peritoneum;mentioning
confidence: 89%
“…Prolonged insufflation with CO2 is associated with a reduction in body temperature as well as the intraperitoneal humidity. [25,34,37] The disadvantages of peri-operative hypothermia are well known and includes increased rates of postoperative infection, increased cardiac output and prolonged postoperative recovery. [25] With respect to the desiccation and temperature factors, there are potential added benefits of using warmed and humidified CO2.…”
Section: Peritoneum;mentioning
confidence: 99%
“…Nach laparoskopischer Cholezystektomie führte die Verwendung eines Niedrigdruck-Pneumoperitoneums im Vergleich zu höherem intraabdominellen Druck zu geringeren postoperativen NRSSchmerz-Scores und einer Reduktion der Analgetikadosis [19,20]. Dagegen führte die Verwendung von angewärmtem Insufflationsgas (37 °C) im Vergleich zu ungewärmtem CO2 in 3 RCT nicht zu einer Reduktion der postoperativen NRS-Scores für Schmerzen [21][22][23]. Gaslose Verfahren zur Anhebung der Bauchdecke hatten in zwei RCT bei laparoskopischen Cholezystektomien gleichfalls nicht zu verminderten postoperativen Schmerzen geführt [24,25].…”
Section: Art Des Pneumoperitoneumsunclassified